Measuring the Influence of Financial Literation and Inclusion on Investment Interest with Social Background as Moderating Variables - Wartoyo; Syaeful Bakhri; Mariyah Ulfa; Rizal Wildan Firdau; Siti Nuraeni; Seli Amelia (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
The lack of Sharia financial literacy leads to a lack of understanding among the public regarding the potential investment opportunities available in the Sharia financial system, causing them to be reluctant to invest. Furthermore, limited Sharia financial inclusion also hinders the increase in investment interest. Limited access to Sharia financial products and services, such as Sharia banking accounts, sharia insurance or sukuk, makes it difficult for the public to engage in investments that align with Sharia principles. This research aims to measure the influence of Sharia financial literacy, Sharia financial inclusion, and social background on the investment interest of Sharia Economics students at IAIN Syekh Nurjati Cirebon. The research population consists of students from the Economics Study Program. A quantitative approach is used in this study. The research sample consists of 88 randomly selected respondents from the population. The results of the analysis show that Sharia financial literacy has a positive and significant influence on the investment interest of Sharia Economics students. Similarly, Sharia financial inclusion also has a positive and significant influence on investment interest. Additionally, both Sharia financial literacy and Sharia financial inclusion have a simultaneous positive and significant influence on investment interest. However, the social background variable does not moderate the relationship between Sharia financial literacy, Sharia financial inclusion, and investment interest.